(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
This research study the properties of Non-Newtonian fluids. Eight samples of Non-Newtonian fluids were prepared, with constant concentration of Carboxy methyl cellulose (CMC) which was (2 gm/500cc), and different concentrations of weighting material (Bentonite). The concentrations of Bentonite were (8, 10, 12, 20, 26, 32, 36, 42) grams with 500 ml water. It was concluded that the increase in the concentration of Bentonite will increase the shear stress with the increase of shear rate. It was also concluded that the increase in the concentration of Bentonite will increase the plastic viscosity, yield point, and density of these Non-Newtonian fluids.